Penanaman Karakter Anak Usia Dini Melalui Metode Dongeng - Mira Yanti Lubis; Rani Astria Silvera Harahap; Mancar Mancar (Institut Agama Islam Negeri Padangsidimpuan, 2020)
The purpose of this study is to find out if a fairy tale method affects the character planting in early childhood. The method used in this research is a type of qualitative study, the subject is a group of PAUD – A SIT Insan Robbani Sibuhuan District of Barumun, Padang Lawas Regency with a range of ages between 4-5 years and a total of 25 people Consists of 15 men and 10 women. The data collection techniques undertaken are by observation and interview methods. The results of the research obtained is through fairy tale methods applied by the teacher obtained very good results and very effective in the cultivation of early childhood characters. This is evident from the changing attitudes and behaviors of children that show a better and positive direction. This is, of course, supported by good examples and refrretion given by teachers to help and foster early childhood characters.